1991
DOI: 10.1073/pnas.88.7.2830
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of cDNAs for two distinct murine tumor necrosis factor receptors demonstrate one receptor is species specific.

Abstract: Complementary DNA clones encoding two distinct tumor necrosis factor receptors were isolated from a mouse macrophage cDNA library. The cDNA for murine tumor necrosis factor receptor type 1 (mTNF-Rl) predicts a mature polypeptide of 425 amino acids that is 64% identical to its human counterpart, whereas the cDNA of murine tumor necrosis factor receptor type 2 (mTNF-R2) predicts a mature protein of 452 amino acids that is 62% identical to human tumor necrosis factor receptor type 2. The two murine tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
267
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 501 publications
(282 citation statements)
references
References 43 publications
(38 reference statements)
11
267
0
4
Order By: Relevance
“…These results were confirmed by qPCR, which showed that livers of Tnfr sf1a +/-mice had about half of the p55TNFR mRNA of Tnfrsf1a +/+ mice (Supplemental Figure 1G). Binding studies using I 125 -labeled human TNF ( 125 I-hTNF), which binds mouse p55TNFR (mp55-TNFR) but not mouse p75TNFR (33), showed that binding is reduced by about half in Tnfrsf1a +/-bone marrow-derived macrophages (BMDMs) compared with Tnfrsf1a +/+ BMDMs ( Figure 1G). Finally, p55TNFR expression was measured on Tnfrsf1a +/-cells by FACS and was intermediate between Tnfrsf1a +/+ and Tnfrsf1a -/-BMDMs (Supplemental Figure 1H).…”
Section: A 50% Reduction Of P55tnfr Completely Protects Mice Against mentioning
confidence: 99%
“…These results were confirmed by qPCR, which showed that livers of Tnfr sf1a +/-mice had about half of the p55TNFR mRNA of Tnfrsf1a +/+ mice (Supplemental Figure 1G). Binding studies using I 125 -labeled human TNF ( 125 I-hTNF), which binds mouse p55TNFR (mp55-TNFR) but not mouse p75TNFR (33), showed that binding is reduced by about half in Tnfrsf1a +/-bone marrow-derived macrophages (BMDMs) compared with Tnfrsf1a +/+ BMDMs ( Figure 1G). Finally, p55TNFR expression was measured on Tnfrsf1a +/-cells by FACS and was intermediate between Tnfrsf1a +/+ and Tnfrsf1a -/-BMDMs (Supplemental Figure 1H).…”
Section: A 50% Reduction Of P55tnfr Completely Protects Mice Against mentioning
confidence: 99%
“…Although, the amino acid sequence homology between mouse and human TNFαισ 79% [81], mouse TNFα (mTNFα) is a glycosylated dimer whereas human TNFα (hTNFα) is not glycosylated [82]. hTNFα does not bind to mouse type 2 TNF receptors (mTNF-R2), whereas mTNFα binds to both mTNF-R1 and mTNF-R2 [83]. Therefore, hTNFα lacks some of the actions of mTNFα in mice [84], so that physiologically relevant effects can only be studied using the homologous cytokines.…”
Section: Tumor Necrosis Factor-αmentioning
confidence: 99%
“…TNFα exerts its effect via two receptors, TNF receptor 1 (TNFR1) and TNF receptor 2 (TNFR2) (Lewis et al 1991;Tartaglia et al 1993;Tartaglia et al 1991). These receptors are localized on neurons, including the nigral neurons, as well as on glial cells (Boka et al 1994;Dziewulska and Mossakowski 2003;McGuire et al 2001).…”
Section: Introductionmentioning
confidence: 99%